Notulae entomologicae. Vol. LV - Meinander, Martin; Panelius, Samuel (Societas entomologica Helsingforsiensis, 2012)
Vol. 55 (1975), N:o 1, s. 1-32 -- Hans Silfverberg : A revision of the genus Laetiacantha Laboissière Coleoptera, Chrysomelidae) -- Eitel Lindqvist : Neue Nematinen aus Sibirien (Hymenoptera, Tenthredinidae) -- Jyrki Muona : Some notes on palaearctic Aleocharinae (Coleoptera, Staphylinidae) -- Martin Meinander : Coniopterygidae from North America (Neuroptera) -- Enkät rörande stora apollofjärilens (Parnassius apollo) försvinnande och nuvarande utbredning — Kysely (iso-)apollon (Parnassius apollo) häviämisestä ja nykylevinneisyydestä -- Litteratur -- Vol. 55 (1975), N:o 2, s. 33-64 -- Hans Silfverberg : A revision of the genus Neolaetana Laboissière (Coleoptera, Chrysomelidae) -- Martin Meinander : Psocoptera from the Mid-Atlantic Islands and Morocco II -- Rauno Linnavuori : Studies on Neotropical Deltocephalinae (Homoptera, Cicadellidae) -- Martin Meinander : Fossil Coniopterygidae (Neuroptera) -- Eduard Wagner : Drei Phytocoris-Arten aus Algérien (Heteroptera, Miridae) -- Pirkka Utrio : Anopheles claviger (Meig.), Aedes pionips Dyar and A. beklemishevi Den. (Diptera, Culicidae) found in Finland -- Litteratur -- Vol. 55 (1975), N:o 3, s. 65-96 -- Svante Ekholm : Fluctuations in butterfly frequency in Central Nyland -- Martin Meinander : Coniopterygidae from South Africa (Neuroptera) -- Larry Huldén : Faunistic notes on Hemiptera from Finland I -- Rauno Linnavuori : On the genus Aphelochirus (Heteroptera, Naucoridae) of tropical Africa -- Walter Hackman : Sten Stockmann in memoriam -- Ingrid Müller-Liebenau & Eino Savolainen : Baetis species from Kuopio Museum, Finland -- Vol. 55 (1975), N:o 4, s. 97-140 -- Wolter Hellén : Die Nematinen Finnlands IV (Hymenoptera, Tenthredinidae) Gattung Pristiphora Latreille -- Martin Meinander : Notes on Plecoptera from Eastern Fennoscandia -- L. N. Medvedev : Coleoptera from North-East Africa. Chrysomelidae: Clytrinae -- Entomologiska Föreningen i Helsingfors — Helsingin Hyönteistieteellinen Yhdistys. Verksamhetsberättelse för år 1974 -- Mötesreferat — Kokousselostuksia